New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia) - Botero, Juan Pablo; Almeida, Lúcia M. (Zootaxa, 2019)
Six new species of Disteniidae are described: Aiurasyma santandereana (Dynamostini), from Colombia; Distenia (D.) marinonii, Distenia (D.) normae, Paracometes solangeae, and Villiersicometes galileoae, all from Brazil, and Novantinoe vivida, from Ecuador (Disteniini). The geographical distribution of 15 species is expanded, and keys to species of Novantinoe Santos-Silva & Hovore, 2007 and American species of Distenia (Distenia) Lepeletier & Audinet-Serville, 1828 are also provided.